1988
DOI: 10.2466/pms.1988.66.3.737
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Enjoyment of Music

Abstract: For 35 participants, 12 men and 23 women, scores on the Tellegen Absorption Scale significantly correlated with ratings of how much they liked music. After completing the scale, each participant listened to eight 4-min. selections of music presented in quasirandom order. These were excerpts from classical, new age, rock, and country music. Each was rated on a scale from 1, for strongly disliked, to 5, for strongly liked. The Pearson correlation of .51 between the Absorption Scale scores and the mean rating sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Levels of absorption in conjunction with listening to music have frequently been measured in laboratory conditions (Kreutz, Ott, Teichmann, Osawa, & Vaitl, 2008;Rhodes, David, & Combs, 1988) using the Tellegen Absorption Scale (henceforth TAS, Tellegen & Atkinson, 1974).…”
Section: Problems In Labelling Experiencementioning
confidence: 99%
“…Levels of absorption in conjunction with listening to music have frequently been measured in laboratory conditions (Kreutz, Ott, Teichmann, Osawa, & Vaitl, 2008;Rhodes, David, & Combs, 1988) using the Tellegen Absorption Scale (henceforth TAS, Tellegen & Atkinson, 1974).…”
Section: Problems In Labelling Experiencementioning
confidence: 99%
“…For example, trait absorption scores are correlated with liking complex (classical in comparison to rock) music [13], a finding that is consistent with the similar trait of openness to experience [4, 14, 15]. In reviewing the literature, however, Roche and McConkey [8] suggested that rather than complexity, the relationship between absorption and liking may be mediated by “personal involvement of a cognitive or an emotional kind with the attentional object” (p. 94).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some swimmers used their stroke tempo to obtain feedback about their performance; hence, they were fully aware of the time factor. A final plausible explanation is that performing synchronously with the music may enhance flow, particularly if the participants enjoyed the music (see Karageorghis & Terry, 1999a;Rhodes, David, and Combs, 1988). There is evidence to suggest that music improves the stylistic elements of movement (Chen, 1985;Spilthoorn, 1986), increases alpha brain wave activity (Burk, 1989;Wales, 1986) and enhances mood state Terry, 1997, 1999b) all of which are precursors of both flow and successful performance (Catley and Duda, 1997;Collins, Powell, and Davies, 1991;Jackson, 1992;Jackson, 1995).…”
Section: Flow State Scale 16mentioning
confidence: 99%